A qualitative study, using focused interviews, of the information needs of families whose children's names are on a cerebral palsy register. - Miller J; Colligan J; Colver A (Child: Care, Health & Development, 2003)
BACKGROUND: We were concerned that information held on a register of children with cerebral palsy was not being made available to contributing families, and that the existence and purpose of the register was not sufficiently understood. METHODS: Focused interviews with 13 families selected by purposive sampling. RESULTS: Many parents would like more information about the data on registers which include their child. They would also like to be more involved in the design of the register and its reports, but there are practical difficulties in making time available for such activity. Although parents were surprised that they had not already been given more information about the existence and purpose of the register, none were resentful that their child's name was on the register once they were reassured about confidentiality and database security. Parents also had general concerns unrelated to the register which were about their need to be treated as equals by professionals, to have more information about equipment and to have earlier and clearer diagnoses. CONCLUSIONS: Registers of children with uncommon conditions have well-established roles in epidemiology, planning and research. By fully involving parents in ways suggested by this study, registers can also empower parents. The study should also provide reassurance to those who hold such registers without explicit consent that the requirement to now obtain consent should not create resentment or jeopardize completeness.